Sensitivity of mixed cation/halide perovskites to evaporation kinetics of DMSO at an early stage. Issue 46 (17th November 2021) - Kim, Gyu Min; Oh, Eun Seo; Jena, Ajay Kumar; Miyasaka, Tsutomu
Abstract : The control of evaporation kinetics depends on perovskite compositions. Abstract : Controlling the evaporation kinetics of the perovskite precursor (EKP) during the thermal annealing step of organic–inorganic hybrid perovskite solar cells (OIHPs) is important for achieving high performance. Although regulation of the evaporation kinetics of precursors and their influence on the final cell performance have been studied, the exact mechanism underlying their effects on the final performance is not understood. In this study, we found that the evaporation kinetics of lead-based organic–inorganic hybrid perovskite precursors strongly depend on the compositions and ratios of cations and halides. Crystal-structure analysis of films of various compositions formed at different stages of thermal annealing revealed that the wet films (before annealing) of lead-based perovskite precursors should be categorised into one of six states depending on perovskite compositions. Interestingly, only two of the six states exhibit a strong dependence on the EKP, implying that extra care should be taken when these perovskite inks are used. We suggest a way to easily determine whether wet films are sensitive to EKP by briefly examining their compositions, without scrutinising their optoelectronic properties. This procedure will help to reduce the standard deviation of the performance and easily obtain high power conversion efficiencies for lead-based OIHPs.